1981
DOI: 10.1080/03014468100005131
|View full text |Cite
|
Sign up to set email alerts
|

Parent-adult offspring correlations and heritability of body measurements in a rural Indian population

Abstract: Mean values and standard deviations of height, sitting height, body weight, biacromial and bicristal diameters, total arm length, upper arm and calf girths and skinfolds at biceps, triceps, below the scapula and at the widest portion of the calf of 67 fathers, 72 mothers and their 99 adult sons and 83 adult daughters belonging to Lewa Patels of rural Gujarat are presented. Sons and daughters showed significantly higher mean values of stature as compared to fathers and mothers respectively. Parent-offspring, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
24
2
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 14 publications
8
24
2
3
Order By: Relevance
“…(8)(9)(10)(11) Both pubertal timing (39) and peak bone mass (40,41) are under the strong influence of hereditable factors and can be moderately affected by common environmental determinants. (42) The hereditable component of pubertal timing was well identified by both twin (43)(44)(45)(46)(47) and mother-daughter relationship (48)(49)(50)(51)(52) studies. Our study both complements and furthers this notion by providing evidence that this familial relationship exists in premenopausal women and their daughters measured at the time of peak bone mass attainment.…”
Section: Discussionmentioning
confidence: 99%
“…(8)(9)(10)(11) Both pubertal timing (39) and peak bone mass (40,41) are under the strong influence of hereditable factors and can be moderately affected by common environmental determinants. (42) The hereditable component of pubertal timing was well identified by both twin (43)(44)(45)(46)(47) and mother-daughter relationship (48)(49)(50)(51)(52) studies. Our study both complements and furthers this notion by providing evidence that this familial relationship exists in premenopausal women and their daughters measured at the time of peak bone mass attainment.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies suggest that secular increases in stature are predominately increases in leg length (Greulich, 1957;Udjus, 1964 as cited in Malina et al, 2004;Dangour et al, 2002;Fredriks et al, 2005;Malina et al, 2004;Meredith, 1978;Moore, 1970;Sanna and Sorro, 2000;Tanner et al, 1982;Vercauteren et al, 1998), results from other studies are not entirely consistent or easily interpreted with available information (Greulich, 1976;Himes, 1979;Kaur and Singh, 1981;Kromeyer-Hauschild and Jaeger, 2000;Leung et al, 1996;Malina et al, 2004;Sanna and Soro, 2000). Several studies have reported gains in mean height but no increases in mean relative leg length in either sex (Greulich, 1976;Kaur and Singh, 1981;Kromeyer-Hauschild and Jaeger, 2000). Others have reported significant increases for males, but not females (Himes, 1979;Malina et al, 2004), and at least one study reports noticeably greater increases in relative leg length among females, but not males (Leung et al, 1996).…”
mentioning
confidence: 89%
“…In comparisons of cross-sectional values from age groups prior to growth completion, reductions in stunting may be difficult to distinguish from increases in maturational tempo (Hauspie et al, 1996). However, even where skeletal growth is likely to have been complete in most or all participants, studies have not consistently found increases in leg length greater than those for sitting height (Greulich, 1976;Himes, 1979;Kaur and Singh, 1981;Leung et al, 1996;Malina et al, 2004).…”
mentioning
confidence: 94%
“…Adult height, or stature, is an ideal quantitative phenotype that is well suited for linkage analysis: it is measured easily and reliably, and is highly heritable with h 2 values ranging from 0.4 to 0.8 [1][2][3][4][5]. Height usually follows a normal distribution and is thought to be polygenic in nature.…”
Section: Introductionmentioning
confidence: 99%